1995
DOI: 10.1093/clinids/21.5.1318
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Q Fever of Pregnancy Presenting as Coxiella burnetii Placentitis: Successful Outcome Following Therapy with Erythromycin and Rifampin

Abstract: Chronic Q fever has been associated with endocarditis, granulomatous hepatitis, and osteomyelitis but only rarely with pregnancy. The apparent predilection of Coxiella burnetii, the organism causing Q fever, for the human placenta suggests that chronic Q fever of pregnancy is due to placentitis. We describe a patient with chronic, clinically apparent Q fever in pregnancy and a successful outcome. The diagnosis was made both by serology and by isolation of C. burnetii from the patient's serum and placenta. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 10 publications
0
19
0
4
Order By: Relevance
“…Because C. burnetii is found in the placenta of aborted fetuses [11], [19], we investigated the ability of C. burnetii organisms to infect BeWo trophoblasts. We extended the previously described procedure for establishing macrophage infection by C. burnetii [20] to BeWo trophoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Because C. burnetii is found in the placenta of aborted fetuses [11], [19], we investigated the ability of C. burnetii organisms to infect BeWo trophoblasts. We extended the previously described procedure for establishing macrophage infection by C. burnetii [20] to BeWo trophoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Before the common usage of hydroxychloroquine, a combination of rifampin plus doxycycline was sometimes used for the treatment of Q fever endocarditis [28,29]. Rifampin has also been used to treat Q fever during pregnancy [58,59]. A combination of rifampin and erythromycin has resulted in a successful delivery and recovery from a human placental infection [58].…”
Section: Alternatives For Q Fever Treatmentmentioning
confidence: 99%
“…Rifampin has also been used to treat Q fever during pregnancy [58,59]. A combination of rifampin and erythromycin has resulted in a successful delivery and recovery from a human placental infection [58]. Rifampin is placed in pregnancy category C by the US FDA.…”
Section: Alternatives For Q Fever Treatmentmentioning
confidence: 99%
“…Findings of Sarkar et al suggest that gestational exposure to azithromycin is not associated with an increase in the rate of major malformations above the baseline of 1-3%, supporting earlier research showing that macrolide antibiotics are generally safe in pregnancy [20]. Bental et al reported a case of chronic Q fever due to placentitis in which treatment with erythromycin and rifampin contributed to the delivery of a healthy baby [21].…”
Section: Discussionmentioning
confidence: 80%